Assessment of Mineral Contents and Technological Properties of Dry Bean Genotypes Grown Under Organic Farming Conditions With Multivariate Analysis - Oğuz Erol; Oğuzhan Uzun; Satı Uzun; Hamdi Özaktan (Journal of Agricultural Sciences)
Beans are an important source of essential minerals such as iron, zinc, calcium, and magnesium, which play a crucial role in various physiological functions. The mineral contents of beans are vital in ensuring a balanced and healthy diet, as these minerals are involved in bone health, immune system function. Additionally, the technological properties of beans, including cooking time, water absorption capacity, and swelling capacity, are important in determining their culinary applications and consumer acceptance. The cooking quality and number of seeds destructed after cooking of beans significantly influence their palatability and overall consumer satisfaction. Assessing the technological properties of different bean genotypes grown under organic farming conditions allows researchers to identify genotypes with desirable cooking characteristics and texture, leading to improved consumer acceptance and culinary applications. Organic farming practices aim to produce food without the use of synthetic chemicals, promoting environmental sustainability and ensuring the production of high-quality and nutritious crops. In this research, 20 bean genotypes were grown under organic conditions for 2 years. To analyze the complex data obtained from the assessment of mineral contents and technological properties of beans, multivariate analysis techniques(correlations, cluster, scatter plot, biplots etc.) are employed. There was a positive relationship between cooking time and Ca mineral. There was a negative relationship between the coefficient of hydration and water absorption capacity and Zn mineral. Positive correlation between Fe, Mn, Cu, Mg, K, P and S elements was observed. Likewise, examining one of the dry weight, dry volume, wet weight, wet volume, water absorption capacity and swelling index values, which are clustered in the same region and have approximately the same axis length, can save time and consumable. The zinc, sodium, iron, and copper contents in the beans grown under organic conditions were found to be higher than the data reported in the literature.